2018
DOI: 10.1111/dmcn.13960
|View full text |Cite
|
Sign up to set email alerts
|

Power mobility for children: a survey study of American and Canadian therapists’ perspectives and practices

Abstract: Occupational and physical therapists positively view early introduction of power mobility for children with mobility limitations. Few therapists actively provide early power mobility experiences. Power mobility training and monitoring power mobility devices are important therapist roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In some studies, practice time has been identified as an important factor in proficiency. Other studies, including the results of the current study, did not find significant associations between practice time and proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In some studies, practice time has been identified as an important factor in proficiency. Other studies, including the results of the current study, did not find significant associations between practice time and proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…5,28 It is important to continue to follow the emergence of access technologies such as motor control via brain-computer interfaces, voice and eye activation, and face recognition, which may prove to be more efficient, and intuitive modes for individuals with severe physical and cognitive disabilities. 29 In some studies, 13,17 practice time has been identified as an important factor in proficiency. Other studies, 24 including the results of the current study, did not find significant associations between practice time and proficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that children with severe limitations can learn powered mobility skills (Bottos et al, 2001;Durkin, 2009;Kenyon et al, 2016;Nilsson, 2019). Many, however, are denied access to independent mobility due to their limited cognitive, physical or behavioral abilities rather than being provided with practice opportunities (Kenyon et al, 2018b;Nisbet, 2002). A systematic review of powered mobility training methods concluded that there is only moderate evidence to support teaching powered mobility, and recommended additional research regarding power mobility training methods for children (Kenyon et al, 2018a).…”
mentioning
confidence: 99%